A “habitação social de mercado” como ativo no mercado de locação e revenda residencial: o caso dos imóveis do PMCMV - Faixa 2 em São José Do Rio Preto-SP - Rodrigues, Thais Borges Martins (2020)
The model of access to housing conditioned by bank financing was the strategy adopted by the Brazilian government in the 2000s, with the “Minha Casa Minha Vida” Program (PMCMV), in line with the promotion of real estate capital, which implied the absence of a public policy capable of providing ample access to real estate credit for families with lower incomes and, as a consequence, limited the exercise of the right to housing. This strategy contributed to the consolidation of the idea of home ownership and to the transformation of the house into more than a place of residence, essential to the maintenance of human life and the reproduction of its workforce, starting to be seen as an asset with a patrimonial dimension. and expectations of future social and economic security, in a rentier dimension that is constantly changing with securitization. In this research, the use of properties originating from the PMCMV is problematized, especially those intended for families with income between three and six minimum wages, the main focus of the program's performance, as a source of generating extra income for its owners in the residential rental market. the same time that public social rental policies are non-existent or little explored, taking as a case study real estate produced by publicly traded companies in São José do Rio Preto, between the years 2009 and 2015. Based on questionnaires applied by the survey method, and analysis of the data referring to the profile of the residents and the territorial and social conditions for the form of appropriation of such properties, there was the creation of a real estate park for residential leasing, composed of different types of properties, especially in the northern region of the country. municipality, where the real estate valuation is lower than the rest of the city, implying a lower housing price. In addition to the price, factors such as the offer of leisure equipment and private security proved to be important aspects for the choice of locations by the tenants, even though it means greater distance from the central areas and less urban infrastructure available. Throughout this work, the decisive role of private real estate agents for the offer of housing and the public authorities was also decisive in contributing to the free sale of these properties in the formal rental market.